ASSESSMENT OF THE SAVINGS OF UKRAINIAN HOUSEHOLDS IN CONDITIONS OF UNCERTAINTY - Гнидюк, Інна; Маршук, Ліна (Modern engineering and innovative technologies, 2024)
Household savings are an important element of financial stability and economic development of the country. In the conditions of economic and political uncertainty in Ukraine, the problem of savings becomes especially important, because the ability of hous